Theory to Process to Practice: A Collaborative, Reflective, Practical Strategy Supporting Inservice Teacher Growth - Inouye, Martha; Houseal, Ana (Innovations in Science Teacher Education, 2018)
To successfully implement the Next Generation Science Standards (NGSS), more than 3.4 million in-service educators in the United States will have to understand the instructional shifts needed to adopt these new standards. Here, based on our recent experiences with teachers, we introduce a professional learning (PL) strategy that employs collaborative video analysis to help teachers adjust their instruction to promote the vision and learning objectives of the Standards. Building on effective professional development characteristics, we created and piloted it with teachers who were working on making student thinking visible. In our setting, it has been effective in providing relevant, sustainable changes to in-service teachers' classroom instruction.